Case report: Double filtration plasmapheresis (DFPP) for severe rhesus-D alloimmunization in two pregnant patients - Liang, Yuling; Wang, Tenghui; Zhu, Wenjian; Wang, Xiaohua; Zhang, Xuemei; Zheng, Zhihua; Lei, Yan (Frontiers in Pediatrics, 2023)
Maternal erythrocyte alloimmunization is one of the most important causes of fetal anemia. The standard treatment for anemic fetuses is intrauterine blood transfusion (IUT). However, IUT may have adverse effects, particularly before 20 weeks of gestation. In this report, two women who had previously had severely affected alloimmunized pregnancy developed high titers of anti-D antibodies before 20 weeks of gestation. Ultrasound Doppler showed severe fetal anemia, and intrauterine transfusion was expected to be unavoidable. To prolong pregnancy to a gestation in which intravascular IUT was possible, we used repeated double filtration plasmapheresis (DFPP) as a rescue therapy. The titers of IgG-D, IgG-A, and IgG-B decreased after DFPP treatment. One woman successfully prolonged pregnancy until 20 weeks of gestation. Subsequently, she underwent four cycles of IUTs and delivered at 30 weeks of gestation by emergency cesarean section due to fetal bradycardia during the fifth intrauterine transfusion. The other woman successfully delayed intrauterine transfusion until 26 weeks of gestation. The favorable results of the two patients indicate that DFPP may be an effective and safe treatment modality for RhD immunity in pregnant women. Moreover, DFPP is potentially helpful for reducing the occurrence of ABO hemolytic disease in neonates due to the clearance of IgG-A and IgG-B antibodies (e.g., O pregnant women harbored A/B/AB neonates). However, more clinical trials are needed to verify the results.